2008
DOI: 10.1089/lap.2008.0137
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Anorectal Malformation in Boys: A Multicenter Study

Abstract: The laparoscopic approach of high imperforate anus allowed an easy control of the fistula and helped to determine the accurate passage through the levator ani. Nevertheless, technical points have to be improved,such as coprostasis before fistula section to avoid stool leakage, rectum tacking to prevent prolapse,and calibration of muscle channel to avoid stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…The dissection at this step in the procedure should also not be too close to the bowel to avoid injury. In addition, an insufficient muscle channel may lead to stenosis [31]. In our series, muscle channel stenosis was found in 1 patient treated with LAARP postoperatively and was relieved by anorectal dilations for 3 weeks.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The dissection at this step in the procedure should also not be too close to the bowel to avoid injury. In addition, an insufficient muscle channel may lead to stenosis [31]. In our series, muscle channel stenosis was found in 1 patient treated with LAARP postoperatively and was relieved by anorectal dilations for 3 weeks.…”
Section: Discussionmentioning
confidence: 55%
“…In this study, we found that 3 patients in the LAARP group and 4 patients in the PSARP group with poor muscle quality developed prolapse, suggesting that muscle quality may be one of the factors to determine postoperative mucosal prolapse. Podevin et al [31] suggested that the extensive dissection of rectum and pelvis could maximize division of the anatomic attachments between the posterior rectum and sacrum and aggravate bladder and sphincter nerve plexus trauma. It is also suggested that to avoid damage, care should be taken when the dissection reaches the bladder neck, prostate, or lower end of the uterus [10].…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, minimally invasive surgery has also influenced the surgical treatment of ARM [28][29][30][31][32][33][34]. LAARP was proposed especially for ''high'' types of ARM such as rectobladderneck and rectoprostatic fistulas [31] in which the rectum is not reachable posterior-sagittally.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic-assisted anorectoplasty is associated with some technical difficulties and complications. These include a residual posterior urethral diverticulum, stool leakage from the distal rectum during the procedure, rectal prolapse, and anal stenosis [15,16]. In addition, laparoscope dissection in a narrow operative space like the pelvis of a small infant can be a very challenging proposition.…”
Section: Discussionmentioning
confidence: 99%